2020
DOI: 10.1016/j.anr.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Respiratory Rehabilitation Program on Perceived Self-Efficacy and Dyspnea in Patients with Lung Cancer

Abstract: This study aims to examine the effects of the respiratory rehabilitation program on perceived self-efficacy and dyspnea in patients with lung cancer. Methods: This is a quasi-experimental research study with a two-group repeated measures design with the pretest and post-test at Week 4 and Week 8. The theory of self-efficacy by Bandura was used as the conceptual framework. The sample consisted of patients with nonesmall-cell lung cancer Stage 4 who visited the oncology clinic in a university hospital. Twenty-ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
(33 reference statements)
0
4
0
1
Order By: Relevance
“…Nursing staff invite patients with good and positive attitude to give speeches to stimulate the emotions and attitudes of other patients, encourage, and support each other, thereby effectively improving their sense of meaning in life [18]. Negative emotions and physical and mental stress of NSCLC patients will affect their treatment effect and even increase the toxic and side effects of radiotherapy and chemotherapy, affect their physical and mental status, increase the burden on patients' families, and reduce their quality of life [19]. Routine nursing intervention is difficult to correct the negative emotions of patients, resulting in insufficient self-efficacy and meaning of life and negative treatment of survival and treatment, affecting their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing staff invite patients with good and positive attitude to give speeches to stimulate the emotions and attitudes of other patients, encourage, and support each other, thereby effectively improving their sense of meaning in life [18]. Negative emotions and physical and mental stress of NSCLC patients will affect their treatment effect and even increase the toxic and side effects of radiotherapy and chemotherapy, affect their physical and mental status, increase the burden on patients' families, and reduce their quality of life [19]. Routine nursing intervention is difficult to correct the negative emotions of patients, resulting in insufficient self-efficacy and meaning of life and negative treatment of survival and treatment, affecting their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, the greater the self-efficacy an individual possesses, the greater the positive effect of persistence and effort on their behavior and the higher the level of mental health. More and more studies have shown that improving self-efficacy plays an important role in the management of chronic and mental illnesses [ 21 ]. Most patients with ARF are depressed and pessimistic, so psychological support is the key to alleviating their psychological pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Se encontraron 10 artículos que muestran resultados relacionados con la sintomatología experimentada y tratada en personas con cáncer de pulmón; los principales hallazgos señalan que los síntomas más frecuentes son, la tos, expectoración, fatiga y disnea, siendo esta última la más común (45) . Las prácticas de autogestión más utilizadas para aliviar la disnea son: el uso de oxigenoterapia y administración de broncodilatadores por encima de las dosis prescritas (40) ; así mismo, la utilización de terapia Fan-to-face es efectiva para aliviar la disnea en pacientes con cáncer terminal (46) y la rehabilitación respiratoria se describe como recurso fundamental para el manejo de los síntomas y la mejora de la autoefi cacia (42) . En lo que respecta al personal de salud, expresa que la tos es una preocupación clínica para la atención de las personas, siendo los opiáceos la estrategia farmacológica más efectiva para tratarla (41) .…”
Section: Barriers To Delivering Advanced Cancer Nursingunclassified